Improved Cardiovascular Function in Old Mice After N-Acetyl Cysteine and Glycine Supplemented Diet: Inflammation and Mitochondrial Factors. (10th March 2018) - Cieslik, Katarzyna A; Sekhar, Rajagopal V; Granillo, Alejandro; Reddy, Anilkumar; Medrano, Guillermo; Heredia, Celia Pena; Entman, Mark L; Hamilton, Dale J; Li, Shumin; Reineke, Erin; Gupte, Anisha A; Zhang, Aijun; et al.
Abstract: Metabolic, inflammatory, and functional changes occur in cardiovascular aging which may stem from oxidative stress and be remediable with antioxidants. Glutathione, an intracellular antioxidant, declines with aging, and supplementation with glutathione precursors, N-acetyl cysteine (NAC) and glycine (Gly), increases tissue glutathione. Thirty-month old mice were fed diets supplemented with NAC or NAC+Gly and, after 7 weeks, cardiac function and molecular studies were performed. The NAC+Gly supplementation improved diastolic function, increasing peak early filling velocity, and reducing relaxation time, left atrial volume, and left ventricle end diastolic pressure. By contrast, cardiac function did not improve with NAC alone. Both diet supplementations decreased cardiac levels of inflammatory mediators; only NAC+Gly reduced leukocyte infiltration. Several mitochondrial genes reduced with aging were upregulated in hearts by NAC+Gly diet supplementation. These Krebs cycle and oxidative phosphorylation enzymes, suggesting improved mitochondrial function, and permeabilized cardiac fibers from NAC+Gly-fed mice produced ATP from carbohydrate and fatty acid sources, whereas fibers from control old mice were less able to utilize fatty acids. Our data indicate that NAC+Gly supplementation can improve diastolic function in the old mouse and may have potential to prevent important morbidities for older people.